1967
DOI: 10.2118/1518-pa
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Filtration During Microbit Drilling

Abstract: Drilling tests with a Ilk-in. diameter roller bit w.we perjormed on Berea and Bandera sandstones and Leuders Iime.$tone lising water (.tnd two conventional drilling muds us circulating f7uids to evaluate the influence of dynamic fi[trationon penetration rate. The muds possessed widely difierirrg API fluid-loss properties. Mud filtrate was constrained to f70w benea(h the bit: no filtrare fiowed radially (hrough the borehole wall. Rock pore pressure at three different loca/ic)ns ahead ojtltebit, cl~mu[ative fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A large skin pressure drop is predicted for the rocks with high permeability because ofthe contrast in fluid diffusivity between the skin and the formation. 6. A significant pressure invasion is shown to take place at the depth of cut for the entire range of rock permeabilities (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A large skin pressure drop is predicted for the rocks with high permeability because ofthe contrast in fluid diffusivity between the skin and the formation. 6. A significant pressure invasion is shown to take place at the depth of cut for the entire range of rock permeabilities (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…10 3. Measurements of permeability as a function of depth ahead of the bit during microbit experiments 6 The skin transmissibility goes to T=4.59 md/m once the mudcake has been wiped out and to T= 121 md/m after the second operation. This clearly shows that all the permeability damage is very superficial, even in highly permeable rocks.…”
Section: Skin Effectmentioning
confidence: 99%
“…n numbers of regression trees are built on the n separated bootstrapped samples [20]. The n averaged predictions are explained by Equation (8).…”
Section: Baggingmentioning
confidence: 99%
“…An increase in MSE means that the system is foundering, and a disproportionate amount of energy is used for the given ROP. Young [8] demonstrated that ROP is influenced by the pressure gradient ahead of the bit. The latter cannot be measured in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Microbit drilling experiments have provided valuable insight into the mechanisms affecting rate of penetration by eliminating field variables. [7][8][9] Whether such experiments simulate full-scale equipment under downhole conditions, however, is questionable.…”
Section: Introductionmentioning
confidence: 99%